2021
DOI: 10.15517/rbt.v69i2.44835
|View full text |Cite
|
Sign up to set email alerts
|

Phenology of the endangered palm Ceroxylon quindiuense (Arecaceae) along an altitudinal gradient in Colombia

Abstract: Introduction: Understanding the phenology of plant populations is vital for their conservation and management. We studied the vegetative and reproductive phenology of the endangered palm Ceroxylon quindiuense along an altitudinal gradient in the Central Cordillera of Colombia. Objective: We describe the leaf production rate, and flowering and fruiting cycles, and calculate food offer for the fauna, as a tool for the proper management of the palm. Methods: At each sampling site (2 400, 2 600, 2 800, 3 000 m.a.s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Moreover, our studied species was also characterized for showing relatively long phenophases. Several palm species show extended phenophases or Martínez et al, 2021). Therefore, a lack of correlation or low correlations between abiotic variables and phenology are a common finding (Henderson et al, 2000).…”
Section: General Phenology and Seasonalitymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, our studied species was also characterized for showing relatively long phenophases. Several palm species show extended phenophases or Martínez et al, 2021). Therefore, a lack of correlation or low correlations between abiotic variables and phenology are a common finding (Henderson et al, 2000).…”
Section: General Phenology and Seasonalitymentioning
confidence: 99%
“…Different flowering phenologies have been proposed to explain the coexistence of highly related plants (Martin et al, 2007;Pascarella, 2007;Spriggs et al, 2019: Pereira et al, 2022. However, the phenology of most tropical palms remain unknown, with few studies focusing on dominant species (Mendes et al, 2017;Pedroso et al, 2021), species useful to humans (Silva & Scariot, 2013), or species that are in danger of extinction (Martínez et al, 2021). Although palm phenological behavior can be highly variable (Henderson, 2002), seasonal and synchronized flowering (De Steven et al, 1987;Ibarra-Manríquez, 1992;Castro et al, 2007;Genini et al, 2009) and continuous flowering throughout the year (Martén & Quesada, 2001;Genini et al, 2009) are the most common behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…There are other relevant studies on another species of Ceroxylon. Martínez et al (2021) found that C. quindiuense flowered sequentially along an altitudinal gradient, thus providing a constant food source, in the form of staminate inflorescences, to pollinating insects. Kirejtshuk & Couturier (2009) collected five species of Mystrops from a single staminate inflorescence of C. quindiuense in Peru, four of them undescribed species.…”
Section: Ceroxylonmentioning
confidence: 99%